(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2024)
The study aims to present some proposals to try to reduce the spread of this phenomenon. The study also aims to develop some proposals to guarantee the rights of divorced women and the rights of their children from a social and economic perspective. The study used the case study approach and relied on the case study guide tool (interview guide). The sample size was (2) two divorced women, and they were drawn using a non-random, intentional sampling method. The study reached the most prominent results, which were represented by proposals to reduce the spread of the phenomenon of divorce, including: The family should not interfere in choosing a life partner, because it is considered one of the reasons for divorce, as is marital infidelity by the husband. There are also proposals to guarantee the rights of divorced women, including providing housing, health insurance for the divorced woman and her children, giving her full dowry, and giving alimony to the divorced woman during the divorce period.